Solar powered portable charger for disaster recovery: design and development using mini solar panel and arduino microcontroller - Abu Bakar, Rashidah; Gunawan, Teddy Surya; Kartiwi, Mira (LAP Lambert Academic Publishing, 2013)
This book presents the development of solar powered portable charger to charge mobile phone during disaster recovery. It emphasizes on efficient solar energy harvesting circuit for charging mobile phone battery with the utilization of intermediate battery. In this book, Sealed Lead-Acid (SLA) battery was chosen as intermediate battery to protect the Lithium Ion battery which seems very sensitive to overcharging and discharging. Concerning on delivering the most efficient portable charger, polycrystalline silicon solar panel was selected which may supply up to 400mW of average power. In addition, Pulse Width Modulation (PWM) charging method was employed using Arduino microcontroller. During disaster, main power supply will be interrupted. If only the victims can communicate through their mobile phone, there will be high chance that they can be rescued by the rescue team. Note that, the portable cell tower can be set up by the relevant authorities during disaster. This book can benefit government, NGO, or volunteers during disaster, as well as many people in disaster prone area.